University Students’ Speaking Anxiety in a Papuan EFL Classroom: A Qualitative Case Study - Ince Rezky Naing; Windy Puspitasari Suparto; Precilia Rafra (FOSTER: Journal of English Language Teaching, 2026)
Speaking anxiety remains one of the most persistent affective barriers that hinders students’ oral performance in English as a Foreign Language (EFL) classrooms, particularly in contexts with limited exposure to English communication. This study aims to explore how university students experience speaking anxiety, identify classroom situations that trigger anxiety, examine its influence on participation and oral performance, and investigate students’ coping strategies in a Papuan EFL classroom. A qualitative case study design was employed involving 20 second-semester English Education students at a public university in Papua. Data were collected through classroom observations, semi-structured interviews, and written reflections over eight weeks, and were analyzed thematically. The findings reveal that students experience anxiety through nervousness, fear of negative evaluation, and low self-confidence, which often lead to silence, hesitation, and avoidance of speaking tasks. Anxiety was particularly triggered by public speaking, spontaneous questioning, and peer judgment. These conditions reduced students’ fluency and participation. However, students adopted coping strategies such as preparation, peer collaboration, and repeated practice to manage their anxiety. The study highlights the importance of supportive classroom climates and low-pressure communicative activities to foster students’ confidence and oral engagement in EFL learning.